El romanticismo como referente para una propuesta pictórica del paisaje del cantón Saraguro - Sauca Lozano, Carlos Mauricio (2015)
This piece of work tries to know in general the characteristics of the romanticism era in painting and especially its aesthetics, to develop a pictorial proposal taking into account the natural environment of the town of Saraguro. At first instance the historical context of landscaping is analyzed, then to later review the theories of such time considering the fundamental theory of Edmund Burke about the sublime and conclude with the artistic proposal. This knowledge acquired during the research process is reflected in the final work whose main purpose is to shape the landscape of the town of Saraguro; incorporating pessimistic emotions that are part of the human mind towards life. To achieve the desired objectives a theoretical and practical research is required, methods and techniques of artistic research is used as needed during the process as is the inductive method that through analysis allows the systematization of information obtained through bibliographic documents and thus their respective interpretation. It starts from the observation and experimental method that allows to combine both the practical part with the theoretical; the techniques used are observation, survey and interview. Based on photographs, drawings, videos, etc., which allows a better approach to the subject of matter. This way it is possible to know the important aspects of the investigation theme and fuse the plastic proposal with knowledge.